Legalization of Medical Marijuana in Indonesia from the Human Rights Perspectives: Lessons Learned from Three ASEAN Countries - Yustina, Endang Wahyati; Simandjuntak, Marcella Elwina; Nasser, Mohamad; Blum, John D; Trajera, Sheilla M. (Lex Scientia Law Review, 2023)
Marijuana (cannabis) as a therapeutic medication has been used and recognized as part of the health system in several countries. In contrast, marijuana in Indonesia is classified as a class I narcotic under Law Number 35 of 2009 on Narcotics, which is prohibited and cannot be used as medication. However, a detailed examination of the Narcotics Act reveals some loopholes and ambiguities that could be exploited to legalize marijuana as a medication to cure certain illnesses. The present study employs normative legal research, specifically a statutory approach, to justify using marijuana for medical purposes. In addition, a legal comparative method is also used in this study to analyze the use of medical marijuana in three ASEAN countries: Thailand, Malaysia, and Singapore. Despite having a reputation for having highly stringent regulations on narcotics, Indonesia can benefit from the experiences of other ASEAN nations, such as Singapore and Malaysia, who have legalized medical marijuana. This consideration is prompted by the fact that certain individuals have shared positive outcomes from using ‘illegal’ medical marijuana as a form of health treatment. However, it is disheartening to note that these individuals have also had to witness the unfortunate loss of their loved ones and, in some cases, face legal consequences such as imprisonment. Conducting comprehensive research on the use of medicinal marijuana in Indonesia is crucial to upholding the citizens' right to health, as the right to health is a significant component of human rights.